Violations of workers’ rights and exposure to work-related abuse of live-in migrant and live-out local home care workers – a preliminary study: implications for health policy and practice - Ohad Green; Liat Ayalon (Israel Journal of Health Policy Research, 2018)
Abstract Background Home care workers work in an isolated environment, with limited supervision and guidance which makes them more prone to abuse and exploitation. While past research focused mostly on the well-being of care recipients, this study aimed to shed light on the care workers’ daily reality and explore if and how boundaries of professional care work are blurred. Our primary aim was to assess the working conditions and the prevalence of abuse and exploitation among live-in migrant home care workers and live-out local home care workers. Methods A random stratified sample of Israeli older adults aged over 70, who are entitled by law to home care services was used to recruit 338 migrant live-in home care workers and 185 local live-out home care workers to a face-to-face survey. The participants were asked about their relationship with the care recipient and their exposure to violations of workers’ rights and work-related abuse. Results Almost all the participants reported exposure to certain workers’ rights violations. Among the migrant live-in care workers, it was found that 58% of them did not receive any vacation days besides the weekly day-off, about 30% reported not get even a weekly day-off on a regular basis, and 79% did not get paid sick days. Local live-out care workers also suffered from a high prevalence of exploitation - 58% did not get any vacation days besides the weekly day-off, and 66% did not get paid sick leave. 20% of the local live-out care workers, and 15% of the migrant live-in care workers did not receive a signed contract. A smaller portion (7.4% among migrant care workers, 2.5% among local care workers) reported work-related abuse. When compared to local workers, migrant home care workers were more vulnerable to some worker’s rights violations, as well as emotional abuse. Conclusion These findings are disturbing, as work-related abuse and exploitation affect not only the well-being of the care worker but also the health of the care recipients, as the quality of care provided deteriorates. At the public policy level, more significant attention and regulation of the home care industry is needed. The frequency and the nature of home visits made by home care agencies must be changed. Also, home care workers should be offered emotional support.